CHANGING FOOD SUPPLY THROUGH NEW IRRIGATION APPROACHES - Kadirov Rakhmatilla Numonovich (Galaxy International Interdisciplinary Research Journal, 2024)
This work is devoted to the analysis of information on the state of water supply, new trends in agricultural development, as well as the forecast of food supply in various regions of the world. Information on measures for the correct use of mineral fertilizers in the production of agricultural products is considered.